Strategi Adaptasi Perantau Asal Desa Jungutbatu di Desa Sanur Kaja - Ni Kadek Mia Pradnyantini Sudiarsa; A.A.A. Murniasih; I Ketut Kaler (Department of Anthropology Udayana University, 2022)
The rapid development of tourism in Bali with many tourist visits has caused many to decide to stay. Migrants have various reasons for deciding to migrate and have strategies to survive in a new place. This study examines the factors of the residents of Jungutbatu Village in choosing the decision to migrate and what adaptation strategies are carried out by the nomads. The main problems in this study are related to (1) Factors deciding to migrate (2) Adaptation strategies carried out by immigrants. The theory used is adaptation theory. The approach used in this research is a qualitative approach with a descriptive-qualitative type of research. Data collection techniques in this study used observation, interviews and literature studies. The results of the study revealed that the factors in deciding to migrate consisted of push factors and pull factors. The strategy taken to survive is related to the development of tourism in Sanur Kaja Village with various obstacles faced and the success achieved by the nomads.